A tradição da fazenda-autarquia (Lavoura arcaica) e a dinâmica da cidade-mundo (Estorvo): desejo incestuoso e regressão em dois cenários do desastre - Ismail Xavier (Nuevo mundo - Mundos Nuevos, 2010)
This article focuses on two films, Lavoura arcaica (2001), by L.F.Carvalho (from Raduan Nassar’s novel) and Estorvo (2000) by Ruy Guerra (from Chico Buarque’s novel). It discusses how a common formal choice (first person narration) gives a particular meaning to their specific subject matter: the crisis of the patriarchal order as lived through the experience of a protagonist moved by an incestuous desire and a regressive refusal of the world. The films deal with very distinct social contexts – a family estate from the mid twentieth century and a big city in the year 2000 -, and the similar attitude shared by their protagonists can be seen as a symptom of a moral crisis in fact referred to contemporary Brazil. Recent cinema has expressed this malaise in dramas built around the figure of the father – present and repressive, or absent and lacking. We deal here with two contrasting scenarios of disaster, one lived as tragedy in a closed territory [the patriarchal family], the other lived as a sense of being adrift in a world marked by the dissolution of identities and social boundaries.